Second language learners' comprehension of conversational implicatures in English - Pratama, Hendi; Nurkamto, Joko; Rustono; Marmanto, Sri (Penerbit Universiti Kebangsaan Malaysia, 2017)
Conversational implicature is a case in which a speaker produces a coded utterance to convey certain intent. The listener of the utterance then decodes the speaker’s intent accurately and ‘intuitively’. For instance, a speaker saying that ‘the room is hot’ could mean that the listener is expected to turn on the air conditioner. However, ‘intuition’ tends to work seamlessly for native speakers but it becomes rather problematic for second language learners. This study comes with two questions: ‘what are the most problematic implicatures for second language learners?’ and ‘what are the factors affecting learners’ competence to comprehend implicatures?’ The implicatures discussed in this study are in the form of joint-taxonomy adopted from the studies of Bouton, Grice and Arseneault. The joint-taxonomy produces ten types of implicatures: POPE-Q, Indirect Criticism, Sequential, Minimum Requirement Rule, Scalar, Idiomatic, Quantity, Quality, Manner and Relevance. 110 college students at one university in Indonesia participated in this study. Vocabulary, grammar formal exposure and informal exposure are four variables affecting the students’ competence in comprehending implicatures in English. This research has been influenced primarily by the study of Bouton and Roever. The results of this study show that indirect criticism implicatures are the most problematic implicatures for all groups of respondents. Additionally, this study is able to illustrate how both Bouton’s claim on proficiency and Roever’s claim on exposure as affecting factors of implicature comprehension can be correct at the same time.